Organizational culture and institutionalization. A theoretical framework - Biyikli, Ali Egemen (Technium Social Sciences Journal, 2024)
This article focused on organizational culture and institutionalization. For this purpose, first of all, general objectives are mentioned in the introduction section. Then, the definition of organizational culture and information about the concept are given. Furthermore, general expressions regarding institutionalization and the relationship between organizational culture and institutionalization mentioned.